Understanding the nuances of virtual collaborative research writing among teacher-researchers in Asia-Pacific Region - Villarama, Joseph A.; Fabros, Bench G.; Dela Fuente, Abegail V.; V. Dela Cruz, Lyan Mae Micah; Jardiel, Rhomark DG.; Neupane, Bharat Prasad (Institute of Advanced Engineering and Science, 2025)
Technological advancement in 21st century brought paradigm shift in research and professional development. Teachers engaged in cross-border and virtual collaborative undertakings. This study reports how teachers engaged in virtual collaborative research writing for professional development, particularly hindrances and potential of leveraging virtual collaborative platforms in Asia-Pacific Region. Utilizing hermeneutic phenomenological approach, insights and experiences of 200 purposively selected teacher-researchers from Afghanistan, India, Indonesia, Japan, Malaysia, Nepal, Philippines, South Korea, Thailand, and Vietnam were elicited through in-depth interviews with 10 open-ended questions. Findings revealed four major themes that expound dynamics of virtual collaborative research writing towards professional development among teacher-researchers, foregrounding convenience and accessibility experienced by teacher-researchers with collaborative research. Further, given the benefits of virtual collaborative platforms, results showed that professional skills, research productivity, and efficiency are developed as teacher-researchers continue to work with different people around the world virtually. While there are multiple advantages, challenges in virtual collaboration remain evidently, including technological obstacles, unreliable internet connectivity, and absence of nonverbal cues that impeded productivity and weakened human connections. With these findings affirming transformative potential of virtual collaboration in academic and professional development, it is crucial to emphasizing its importance in overcoming traditional barriers to research, innovation, and professional development.